Software and systems engineering standards life cycle processes - Reilly, Annette (IEEE Communications Society, 2021)
This course shows systems engineers how to use IEEE standards for life cycle processes, understand life cycle and engineering process concepts, select and apply useful systems and software engineering standards, and employ special considerations for the critical programs of defense and aerospace. It helps engineers to prepare for complex issues through interrelated life cycle processes and how to use agile techniques for rapid delivery without sacrificing quality and meeting customer demands.